HISTORY OF UTILIZATION OF THE COMPUTATIONAL FLUID DYNAMICS METHOD FOR STUDY PICO HYDRO TYPE CROSS-FLOW - Dendy Adanta; Dewi Puspita Sari; Nura Muaz Muhammad; Aji Putro Prakoso (Indonesian Journal of Engineering and Science (IJES), 2021)
Energy crisis in particular, electricity in the isolated rural areas of Indonesia is a very crucial issue that needs to be resolve through electrification . Compared to other options, pico hydro cross-flow turbine (CFT) is the better option to provides electrical power for the isolated rural areas. Studies to improve CFT performance can be undertaken analytically, numerically, experimentally, or a combination of those methods. However, the development of computer technology makes numerical simulation studies have become increasingly frequent. This paper describes the utilization of the computational fluid dynamic (CFD) approach in the pico hydro CFT method. This review has resulted that the recommended Renormalization Group (RNG) k-ε turbulence model for CFT CFD simulation because its absolute relative error is lower than standard k-ε and transitional Shear Stress Transport (SST). The absolute relative error for the RNG k-ε turbulence model of 3.08%, standard k-ε of 3.19%, and transitional SST of 3.10%. While for the unsteady approach, the six-degrees of freedom (6-DoF) are considered because more accurate than moving mesh. The absolute relative error for 6-DoF of 3.1% and moving mesh of 9.5%. Thus, based on the review, the RNG k-ε turbulence model and 6-DoF are proposed for the pico hydro CFT CFD study.